PENGARUH PENDAPATAN ASLI DESA DAN ALOKASI DANA DESA TERHADAP BELANJA DESA (Studi Kasus Kecamatan Kabila Bone Kabupaten Bone Bolango) - Ni Ketut Raka; Noholo, Sahmin; Pakaya, Lukman (Al-Buhuts, 2023)
The aim of this study is to determine the effect of original local government revenue and village fund allocation on village expenditure in Kabila Bone Sub-District, Bone Bolango Regency. This research implements a quantitative method with data collection techniques using secondary data on village financial statements. There are 36 samples used in this study from nine villages in Kabila Bone Sub-District, Bone Bolango Regency. In addition, this study used multiple linear regression for its analysis. The result shows that the original local government revenue positively and significantly affects village expenditure in Kabila Bone Sub-District. Besides, the village fund allocation also positively and significantly affects village expenditure in Kabila Bone Sub-district. Based on the two simultaneous variables, which are original local government revenue and village fund allocation, it concludes that those variables positively and significantly affect village expenditure.